Audit Kepatuhan 2 Menilaian Kontrol Internal dalam Studi Literatur - Gilbert Alexander Hendrik Sipahelut; Tri Ratnawati (Jurnal Riset Ekonomi dan Akuntansi, 2023)
Internal audit is a series of processes and techniques in which employees within a company seek certainty about the accuracy of financial information and the course of operations in accordance with what has been determined. Besides increasing the reliability of information and ensuring compliance with management policies, the scope of work of internal audit also includes protection of company assets and assessment of whether resources have been carried out economically and efficiently. Thus it is very clear that internal audit has become a dominant tool for company leaders to monitor and oversee the course of the company's operational activities. Moreover, internal examiners (supervisors) certainly know more about all policies, procedures and various company issues in more detail than external examiners (public accountants).